Workplace-based assessment in healthcare: Key concepts and best practices - Chaoyan Dong; Siew Ching Low; Clement C Yan (Proceedings of Singapore Healthcare)
Workplace-based assessment (WBA) integrates assessment with clinical practice and ensures that healthcare professionals meet required competency standards. This essay discusses WBA's key concepts, such as competency, standards, principles of assessment, rules of evidence, and entrustable professional activities (EPAs). It highlights the importance of aligning assessments with learning objectives and setting clear standards to enhance healthcare education and patient care.